Monitoring the impact of COVID-19 in Myanmar: Agricultural production and rural livelihoods in two irrigation schemes - June 2020 survey round - Lambrecht, Isabel B.; Ragasa, Catherine; Mahrt, Kristi; Aung, Zin Wai; Wang, Michael (International Food Policy Research Institute, 2020)
This policy note provides evidence of the immediate impacts of the COVID-19 crisis on farming communities in Myanmar’s Central Dry Zone using baseline data from January 2020 and follow-up phone survey data. The first round of the phone survey was conducted between 10 and 21 June 2020 and inquired about the effects of COVID-19 on agricultural production and other livelihood sources from February to May 2020. In total, 1,070 male and female respondents from 605 households in 30 communities were interviewed. The sample for the phone survey covers all nonirrigation households and all women-adult-only households (WHH), as these categories of households were few in the baseline survey, and a randomly selected subsample of the dual-adult irrigation households covered in the baseline.